Digital Equity and Inclusion Gaps in Municipal Digital Transformation: A Systematic Review of Global South Evidence - Lekettey, Edem; Muftahudin, Asep (Jurnal Manajemen Pelayanan Publik, 2026)
Municipal digital transformation is increasingly promoted as a pathway for improving public service delivery, administrative efficiency, and citizen participation across cities in the Global South. However, emerging evidence suggests that digitally mediated governance systems frequently generate uneven inclusion outcomes due to variations in institutional capacity, governance arrangements, and sociotechnological inequalities. This study examines how municipal digital transformation shapes digital equity and inclusion outcomes. Through an interpretive thematic synthesis of 57 Scopus-indexed empirical studies, we construct a governance-focused typology conceptualizing municipalities as service providers, platform orchestrators, data stewards, inclusion enablers, and institutional capacity builders within digitally mediated governance systems. Our results indicate that digital inequities emerge not only from access-related issues but also from weak institutional responsiveness, digital governance fragmentation, reliance on platforms, exclusionary service provision, and inconsistent participation. The findings contribute to the literature on digital governance in municipalities, advancing knowledge about digital equality as institutionally and governance-enabled rather than technologically determined. Finally, we highlight the importance of institutional capacity strengthening, inclusive digital governance, and responsible digital platforms to enable public value creation globally, especially in the Global South.